Pengaruh CAR, LDR, BOPO, dan NPL Terhadap Profitabilitas (ROA) Bank Perkreditan Rakyat Kota Malang (Tahun 2018-2021) - Michael Wardana; Pompong B Setiadi (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This research aims to analyze the factors that influence the profitability of Rural Banks (BPR) in the city of Malang. The method used in this study is a quantitative approach using multiple linear regression methods, and the data used is secondary data sourced from the Financial Services Authority (OJK). The data collected is financial report data from 2018 to 2021. The data is processed using the multiple linear regression analysis technique. The results showed that the LDR variable had a positive and insignificant effect on profitability, CAR had a positive and significant effect on profitability, BOPO had a negative and significant effect on profitability, and NPL had a negative and significant effect on profitability.